ANALISIS PENGARUH STRUKTUR MODAL, KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Aning Fitriana; Hanny Gresya (UNPERBA, 2021)
This study aimed to investigate the effect of dividend policy variabel and capital structure to the value of the company. The value of company measured as price too book value (PBV) The research was conducted at Indonesia Stock Excahnge with research periode of 2016-2018. The amount of sample was 33 manufacturing companies. The sample method used was purposive sampling. The method of analysis of this research used multiple linear regression. The result of this research indicated that partly dividend policy variable have significant negative effect to the value of company, whereas capital structure variable have significant postive effect to the value company. Keyword : dividend policy, capital structure, value of the company.